What's the problem with disaster? Anthropology, social work, and the qualitative slot. (November 2021) - Holmes, Tisha Joseph; Mathias, John; McCreary, Tyler; Elsner, James Brian
On March 3, 2019, an EF4 tornado devastated the rural Alabama communities of Beauregard and Smith Station, killing 23 people and causing direct injuries to another 97. This storm was unusually devastating, with twice the predicted casualty rate based on the tornado's power, the impacted population, and impacted housing stock. In this paper, we apply qualitative methods from anthropology, geography, and planning to better understand the social context of this unusually devastating tornado. Recognizing that there are multiple formulations of the problem of disasters, we aim to highlight how interdisciplinary qualitative research can deepen our understanding of tornado disasters. Combining policy analysis, political economic critique, and ethnographic description, we seek to showcase how qualitative research enables us to interrogate and reimagine the problem of disasters. Rather than simply juxtaposing qualitative and quantitative methods, we emphasize how the heterogeneity of qualitative research methods can strengthen interdisciplinary research projects by generating dialogue about the multiple contexts relevant to understanding a social problem. While problem definition remains a central challenge to establishing a dialogue between anthropology and social work, here, we intend to extend this discussion to larger interdisciplinary collaborations. Situating the issue of problem formation within a broader ecology of qualitative inquiry, we highlight how dialogue about problem definition can, itself, produce meaningful insights into how we understand disasters.